MADANIY-OMMAVIY TADBIRLARDA OVOZ REJISSYORINING KASBIY KOMPETENSIYALARI (ART AND CULTURE BULLETIN, 2026)
In this scientific article, the professional role, functional duties, and creativeresponsibility of the sound engineer in the process of effective organization of cultural events areanalyzed from a scientific-theoretical and practical point of view. The role of the sound director ininfluencing the technical knowledge, managing the acoustic environment, balancing the voices ofthe participants in stage processes, and influencing the psychology of the audience is highlightedbased on specific facts. The article reveals the organizational, technological, and creative activitiesof the sound engineer through examples of various cultural events (concerts, theatricalperformances, public holidays, conferences). Also, the development of modern sound technologiesand their impact on the quality of cultural events are analyzed on a scientific basis.